2012
DOI: 10.1007/s00339-012-7341-4
|View full text |Cite
|
Sign up to set email alerts
|

A XANES study of chromophores in archaeological glass

Abstract: Abstract:We applied X-ray Absorption Near Edge Spectroscopy (XANES) to obtain information on the origin of glass color of several archaeological samples and on the oxidation conditions employed during their production. We studied a series of selected glass fragments mainly from excavated primary and secondary production centers and dated to the first millennium AD containing iron and manganese in a wide compositional range. In most of the studied samples iron is rather oxidized, while Mn K-edge XANES data show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 29 publications
4
30
0
Order By: Relevance
“…Data from this study 13‐1: ◯; 13‐2: ▵; 13‐3: ◇; 13‐4: ◻ as original (black plain symbols). Data from previous studies are reported: ❋, ×, ⧖, ▽, black symbols: blue and blue‐green glasses, gray symbols: other colors. Three domains (i), (ii) and (iii) are distinguished (see discussion).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from this study 13‐1: ◯; 13‐2: ▵; 13‐3: ◇; 13‐4: ◻ as original (black plain symbols). Data from previous studies are reported: ❋, ×, ⧖, ▽, black symbols: blue and blue‐green glasses, gray symbols: other colors. Three domains (i), (ii) and (iii) are distinguished (see discussion).…”
Section: Discussionmentioning
confidence: 99%
“…The quantification of the redox ratio from the centroid position of the pre‐edge is complex because of the overlapping contributions of Fe 2+ and Fe 3+ and the dependence of the intensity of each contribution on the chemical composition. The redox ratios presented in this study were estimated from the edge energy position at a normalized absorbance of 0.5 and using two reference soda‐lime glasses (respectively 95 mol% and 10 mol% Fe 2+ evaluated by wet‐chemistry) . We estimated the Cu + concentration from the intensity of the feature at 8984 eV after subtracting the main edge contribution and using one reference soda‐lime glass (containing 45 mol% of Cu 2+ ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Mn-bearing crystalline compounds have already been studied at the Mn K-edge using Si(111), [28][29][30][31][32] Si(220) [33][34][35][36] or even Si(511) monochromator crystals, 37 only few studies present measurements performed using a Si(311) monochromator. 38,39 A set of Mn-bearing crystalline compounds (Table 2) 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 …”
Section: X-ray Absorption Experiments : Crystalline Referencesmentioning
confidence: 99%
“…For example, Gliozzo (2017) recently drew an inventory of a large quantity of Roman decoloured glasses and calculated based on 104 samples that manganesedecoloured glass contains on average 1.10 ± 0.63 wt% of MnO with a maximum of 2.43 wt%. While the 57 purple Roman glass fragments found in the literature contain on average 2.1 ± 0.9 wt% of MnO, the manganese oxide concentration interval goes from 0.95 to 3.82 wt% (Arletti et al, 2013(Arletti et al, , 2010Bonnerot et al, 2016;Boschetti et al, 2017;Cagno et al, 2014;Cosyns et al, 2014;Freestone and Stapleton, 2015;Gallo et al, 2013;Ganio et al, 2012;Mirti et al, 2008;Möncke et al, 2014;Rehren et al, 2015;Rosenow and Rehren, 2014;Schibille et al, 2016;Silvestri et al, 2014;Van Der Linden et al, 2009). There are thus many glasses with virtually the same concentrations in iron and manganese oxides which have totally different colours.…”
Section: Introductionmentioning
confidence: 98%